1950
DOI: 10.1021/ja01165a051
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of the Sulfides of Thorium and Uranium2

Abstract: Since lattice energy calculations have indicated that the most stable sulfides of the periodic system could be expected in the neighborhood of the elements of the rare earth and actinide series, a thorough study of the sulfides of typical representatives of these elements was made. This paper describes the results of the study of the sulfides of thorium and uranium.The earliest careful study of thorium and uranium sulfides is that of Picon4r6sB who studied methods of preparation of ThS2 and US2 and the propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1953
1953
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…Introduction. -Uranium and thorium monosulphides (US and ThS) have at room temperature the NaCI crystalline structure [1] and a metallic electrical conductivity [2]. While ThS shows a small temperature independent paramagnetism [3], US is ferromagnetic below 178 K [4].…”
mentioning
confidence: 99%
“…Introduction. -Uranium and thorium monosulphides (US and ThS) have at room temperature the NaCI crystalline structure [1] and a metallic electrical conductivity [2]. While ThS shows a small temperature independent paramagnetism [3], US is ferromagnetic below 178 K [4].…”
mentioning
confidence: 99%
“…The magnetic susceptibilities are independent of field strength and temperature. In the present studies complexes are weakly diamagnetic as observed [22][23][24] .…”
Section: Magnetic Behaviour Of Complexesmentioning
confidence: 69%
“…The predominant reaction equation for the hydrolysis was found to be T~C I --, N , S~ HzO =ThOz+(l-z)CH&x N&+X/2 H2, and side reactions such as lead to the formation of amines were far less prominent. (2) The absence of higher nitrides through the hydrolysis of ThN was explained by the lattice relation between ThN and the higher nitrides, Th3N4 and Th2N20. A calculation showed that the movement of thorium atoms by 2 a a t least is necessary for the formation of ThsN4 or ThzNzO lattices starting from the ThN lattice.…”
Section: Discussionmentioning
confidence: 99%